Synthesis and characterization of ZIF-8 mixed matrix membranes - Lok, C.C. (Trans Tech Publications Ltd, 2014)
In the present work, ZIF-8/6FDA-durene mixed matrix membranes (MMMs) were synthesized and characterized. ZIF-8 nanocrystals, which were used as the inorganic filler, were synthesized using rapid room-temperature synthesis method whereas 6FDA-durene polyimide was synthesized by polycondensation method followed by chemical imidization. Pure and 6FDA-durene membranes loaded with 5 wt, 10 wt and 15 wt of ZIF-8 were fabricated. The structural properties and morphology of the resultant membranes were characterized by using X-ray Diffraction (XRD) and Field emission scanning electron microscope (FESEM) . The EDX images showed that ZIF-8 particles agglomerated in the polymer matrix. However, no phase separation was observed for all resultant MMMs. Â© 2014 Trans Tech Publications, Switzerland.